Current Air Quality Issues - Nejadkoorki, Farhad; Nejadkoorki, Farhad (IntechOpen, 2015)
Air pollution is thus far one of the key environmental issues in urban areas. Comprehensive air quality plans are required to manage air pollution for a particular area. Consequently, air should be continuously sampled, monitored, and modeled to examine different action plans. Reviews and research papers describe air pollution in five main contexts: Monitoring, Modeling, Risk Assessment, Health, and Indoor Air Pollution. The book is recommended to experts interested in health and air pollution issues.
English
Keywords: Pollution & threats to the environment; Pollution & threats to the environment